Assessing of Effect of an Educational Intervention Based on Pender’s Health Promotion Model on the Medication Adherence of Older Adults With Type 2 Diabetes: A Randomized Clinical Trial - Fatemeh Khorashadizadeh; Rezvan Rajabzadeh; HabibeSadat Shakri; Adeleh Sahebnasagh; Zahra Salehee; Zohreh Abasi (Sālmand)
Objectives Medication adherence of older adults with diabetes is poor and their hemoglobin (Hb) A1C is low. Educational interventions are needed to change their lifestyle. The present study aimed to assess the effect of an educational intervention based on Pender’s Health Promotion Model (HPM) on the medication adherence of older adults with type 2 diabetes (T2D). Methods & Materials This randomized clinical trial was conducted on 80 older adults with T2D refered to treatment centers in Bojnourd, Iran. They were randomly divided into two groups of 40 including intervention and control. Both groups received routine training, but the intervention group received education based on the HPM at 8 sessions for 4 weeks. The data was collected by a demographic information, the Health Promoting Lifestyle Profile-II (HPLP-II), the eight-item Morisky Medication Adherence Scale (MMAS), and the HbA1C test before and three months after the intervention. Data were analyzed in SPSS v.23 software using independent t-test, paired t-test, and linear regression analysis, consideng a significance level of P<0.05. Results The majority of participants (52%) were female and their mean age was 67.5±5.85 years. Comparison between groups showed that the mean scores of all dimensions of HPLP-II and MMAS in the intervention group were significantly higher than those in the control group after the intervention (P<0.001). The level of HBA1C in the intervention group significantly decreased from 7.38±0.657 to 6.94±0.661 compared to the control group (P<0.001). Conclusion The HPM-based educational intervention is recommended for changing the lifestyle and improving the medication adherence and HbA1C of older adults with T2D.